Peran Dividend Policy dalam Memoderasi Pengaruh Investment Opportunity Set Terhadap Stock Return dengan Profitabilitas Sebagai Variabel Kontrol - Fitri Yani; Abdul Rosyid; Fiesty Utami (Owner : Riset dan Jurnal Akuntansi, 2026)
This study examines the effect of Investment Opportunity Set (IOS) on stock return, with dividend policy acting as a moderating variable and profitability as a control variable in companies listed in the LQ45 Index during the 2020–2024 period. The sample was selected through purposive sampling, resulting in 23 companies that met the criteria, with a total of 115 observations. Data analysis was conducted using panel data regression with the assistance of EViews 13, including descriptive statistics, classical assumption tests, hypothesis testing, and interaction testing to examine the moderating effect. Based on the results of the model selection tests, the Random Effects Model (REM) was determined to be the most appropriate model. The findings indicate that IOS has a positive and significant effect on stock return, suggesting that firms with greater growth opportunities tend to generate higher returns. Dividend policy is found to weaken the effect of IOS on stock return, indicating that higher dividend distribution may reduce the strength of the positive relationship between growth opportunities and market returns. Furthermore, profitability functions as an effective control variable, as it is able to isolate the pure effect of IOS and dividend policy on stock return without eliminating their statistical significance. These findings are consistent with agency theory, which posits that dividend policy serves as a mechanism to reduce agency conflicts between managers and shareholders by limiting managerial discretion over free cash flow, thereby influencing how investment opportunities are translated into shareholder returns.